A Conceptual Framework for Implementing a Problem-Solving Based Mathematics Curriculum in Vocational Education - Firdaus, Firdaus; Akib, Irwan; Sukmawati, Sukmawati (PPSDP International Journal of Education, 2025)
This study is a conceptual investigation aimed at developing a theoretical framework for implementing a problem-solving based mathematics curriculum in Intermediate Vocational Schools (SMK). The study is motivated by the need to bridge the gap between conventional mathematics learning approaches and the demands of the industrial world, which require students to possess critical, creative, and adaptive thinking skills. The research employed a systematic literature analysis using reputable international sources indexed in Scopus from 2015 to 2025. The synthesis of the literature reveals five key components of effective implementation strategies: (1) strengthening teacher capacity in designing problem solving oriented learning, (2) developing contextual instructional designs, (3) ensuring strong industry relevance, (4) applying competence-based and sustainable evaluation, and (5) fostering institutional support for innovation. The resulting conceptual framework provides theoretical contributions to the development of vocational mathematics curricula and offers practical guidance for teachers in designing learning activities aligned with the needs of the world of work.